2020
DOI: 10.1002/acn3.51227
|View full text |Cite
|
Sign up to set email alerts
|

Role of homocysteine in the development and progression of Parkinson’s disease

Abstract: Homocysteine is an essential intermediate product of biochemical reactions that is present in various tissues of the human body. Homocysteine may be associated with the development and progression of Parkinson's disease. Plasma homocysteine levels in patients with Parkinson's disease are elevated compared to those of healthy individuals. High homocysteine drives PD development and progression while aggregating the clinical symptoms of PD patients. The relationship between PD and homocysteine involves multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 55 publications
(105 reference statements)
1
33
0
Order By: Relevance
“…Elevated plasma homocysteine levels are known found to be associated with PD 33 and several in-vivo studies have revealed the beneficial results of a low methionine diet on neurodegenerative diseases 33 . In our clinical trial, plasma levels of S-adenosylhomocysteine as well as 2,3-dihydroxy-5-methylthio-4-pentenoate and N-acetyl taurine were significantly decreased on Day 84 vs Day 0 in the CMA group (Figure 3B, Dataset S4).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated plasma homocysteine levels are known found to be associated with PD 33 and several in-vivo studies have revealed the beneficial results of a low methionine diet on neurodegenerative diseases 33 . In our clinical trial, plasma levels of S-adenosylhomocysteine as well as 2,3-dihydroxy-5-methylthio-4-pentenoate and N-acetyl taurine were significantly decreased on Day 84 vs Day 0 in the CMA group (Figure 3B, Dataset S4).…”
Section: Resultsmentioning
confidence: 99%
“…34 High Hcy levels in PD patients can affect many pathways including gene defects, apoptosis, oxidative stress and DNA damage. 22 Hcy may be neurotoxic to the SN due to disruption of the balance of striatal activity, but experimental studies have shown it. The results of experimental studies are different from studies conducted on PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a potential role of OCM in the development of PD [ 226 ]. In accordance with AD, elevated plasma Hcy is evident in approximately 30% of PD patients and is suggested to be involved in the onset and progression of PD [ 227 ]. Hyper-homocysteinemia in PD patients may be aggravated due to the frequent administration of L-DOPA as a treatment to replenish dopamine loss.…”
Section: One-carbon Metabolism and Neurodegenerationmentioning
confidence: 99%